Representation of Moral Messages in Little Mom Film (Roland Barthes' Semiotic Analysis) (Pena Cendekia Insani, 2023)
This research wants to see and examine the meaning (moral message) shown through a film, through the signs in each scene (story scene). The sign in question can be in the form of scenarios, images, text, scenes and so on. These signs are studied using semiotic analysis to find out the hidden meaning of a sign. The film that is of concern to the writer is the film Little Mom. The film Little Mom is based on a 2018 health organization (WHO) journal about the lives of teenage girls who become pregnant out of wedlock. This film tells the story of teenage children by showing the twists and turns of teenage problems between love, dreams and also the future. This study aims to determine the form of the moral message in the film Little Mom and to understand the meaning of the moral message contained in the film Little Mom. This research is a descriptive qualitative research, where this research will analyze, record, describe and interpret the meanings, symbols contained in the film Little Mom related to the meaning of moral messages using the theory of semiotic analysis by Roland Barthes.